Development of Interactive Multimedia Integrated with PBL (Problem Based Learning) in the Subject of Economics for Grade X High School - Setiawati Setiawati; Zelhendri Zen; Nofri Hendri; Rayendra Rayendra (ARMADA : Jurnal Penelitian Multidisiplin, 2026)
Conventional media still dominate economics learning on the topic of demand and supply, so they are not able to help students understand the relationship between concepts in depth or solve contextual economic problems. This condition indicates the need to develop learning media that are not only interactive but also capable of integrating problem-based learning activities. This study aims to develop interactive multimedia integrated with Problem-Based Learning (PBL) in Economics subjects for grade X of Senior High School and test the validity, practicality, and effectiveness of the resulting product. The study used the Research and Development method with a 4-D model that includes the stages of define, design, develop, and disseminate. The research subjects consisted of expert validators, Economics subject teachers, and grade X students of SMA Pertiwi 1 Padang. Data were collected using validation sheets, practicality questionnaires, and learning outcome tests (pretest–posttest), then analyzed descriptively and quantitatively using percentages and the Normalized Gain (N-Gain) index. The results of the study showed that interactive multimedia had a validity of 95.47% (very valid), practicality of 99.59% (very practical), and effectiveness, as indicated by an N-Gain score of 0.84, in the high category. The developed multimedia-integrated PBL syntax used case studies, interactive activities, and evaluations to encourage student involvement in the problem-solving process. These findings indicate that PBL-integrated interactive multimedia is worthy of use as an alternative learning medium to improve the quality of learning and learning outcomes in the demand and supply material.